Internetowy talk-show – odmiana rodzajowa czy nowy gatunek? Charakterystyka programu 20 m2 Łukasza - Barczyk, Agnieszka (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The subject of this paper is a TV show by Łukasz Jakóbiak, „20m2 Łukasza” (“20 square meters of Lucas”), which has aired since May 2012. The program, interpreted as an internet talk-show, is a starting point in discussing the genealogical status of the TV production. The article consists of three parts: the first introduces the elements typical of the talk show, the second concentrates on the show being discussed, and the third tries to answer the provided question. The author proposes three views instead of just one solution: type variety, new genre and a new name for an old product.